Peramalan Suku Bunga Acuan (BI Rate) Menggunakan Metode Fuzzy Time Series dengan Percentage Change Sebagai Universe of Discourse - Wiratama Paramasatya; Dian Eka Ratnawati; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
BI rate is the interest rate policy that reflects the monetary stance policy which set by the Central Bank of Indonesia and announced to the public. BI rate greatly affects the trade, industry, stock prices, and especially banking. If the policy rate set by the Board of Governors is not in accordance with the trend of economic conditions at a certain time it will have a negative impact on the economic condition of Indonesia. This is what causes the importance of BI rate forecasting in the hope that business players can anticipate the long-term impact of BI rate determination. This research implements fuzzy time series using percentage change as the universe of discourse to predict BI rate in certain period. This method focuses on forming the universe of discourse and the development of steps to form an interval. Based on the results of the tests that have been done, using the best variable values ​​are 12 as the initial interval length, 2 as the value of n-topFrequency 2, and 10 as the length of sub-interval produce MAPE of 0.09005%. The final result obtained is the result of BI rate forecasting according to the period that the user wants to forecast.